Toxic Leadership Insights From A Systematic Literature Review Of Quantitative Research In Diverse Sectors - Ninggeding, Lusiana Lusiana Rambu Kahi; Supriharyanti, Elisabeth; Herachwati, Nuri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
A toxic leadership style is a harmful leadership approach that negatively impacts both individuals and organizations. It is distinguished by behaviours like narcissism, intimidation, manipulation, and self-aggrandizement. This study is a systematic literature review of 26 quantitative articles discussing the antecedents, consequences, and mediating and moderating variables of toxic Leadership across various sectors. The findings reveal that toxic leadership triggers stress, burnout, decreased performance, and turnover intention while also fostering a toxic organizational culture. Furthermore, variables such as job satisfaction and organizational culture can mediate its impact, whereas organizational cynicism and masculinity contest culture intensify its effects